2007
DOI: 10.1007/s00265-007-0474-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social experience on cooperative behaviour of rats (Rattus norvegicus): direct vs generalised reciprocity

Abstract: Cooperation among non-kin has been attributed sometimes to reciprocal altruism: Two or more individuals exchange behaviour that benefits the respective partner. According to direct reciprocity, cooperation is based on past behaviour of a known partner. In contrast, in generalised reciprocity, cooperation is based on anonymous social experience where the identity of the partner is irrelevant. In a previous study, female Norway rats (Rattus norvegicus) were found to cooperate according to a generalised reciproci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
226
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(238 citation statements)
references
References 44 publications
10
226
2
Order By: Relevance
“…Positive emotions, like gratitude, can increase the propensity to perform costly social behaviour: after a positive social experience (like receiving a cookie from someone), humans are more helpful and generous in anonymous cooperative tasks [14,15]. If the internal state can motivate individuals to cooperate even with unknown partners, then because of its simplicity, a mechanism of generalized reciprocity merely based on a change of the internal state contingent on the experience of received help would seem much more likely than the direct or indirect types of reciprocity, which require much more specific memory and cognitive ability and effort [19]. Consequently, unravelling the origin and stability of generalized reciprocity as an evolved state-based mechanism could help to understand cooperation among humans and other animals.…”
Section: Introductionmentioning
confidence: 99%
“…Positive emotions, like gratitude, can increase the propensity to perform costly social behaviour: after a positive social experience (like receiving a cookie from someone), humans are more helpful and generous in anonymous cooperative tasks [14,15]. If the internal state can motivate individuals to cooperate even with unknown partners, then because of its simplicity, a mechanism of generalized reciprocity merely based on a change of the internal state contingent on the experience of received help would seem much more likely than the direct or indirect types of reciprocity, which require much more specific memory and cognitive ability and effort [19]. Consequently, unravelling the origin and stability of generalized reciprocity as an evolved state-based mechanism could help to understand cooperation among humans and other animals.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of reciprocity and assuming that bats exhibit no dyadic preferences when aiding non-kin groupmates, non-kin sharing might simply help sustain a larger group of possible donors by increasing survival of roost-mates (via passive group augmentation [9][10][11]). Alternatively, cooperation might be enforced by partner choice, partner control or both [3,[12][13][14][15][16]. This scenario assumes that bats invest in specific social bonds based on the fitness-relevant returns, and it predicts that bats which make better social investments will be more successful even within a group of constant size.…”
Section: Introductionmentioning
confidence: 99%
“…While studying modalities of cooperation among Norway rats, we found that Rattus norvegicus cooperates using direct reciprocity in an iterated prisoner's dilemma, helping preferentially cooperators instead of defectors (Rutte & Taborsky 2008). More recently, in an experiment involving two conspecific cooperators providing test rats with Bappreciated bananas^or Bless appreciated carrots,^we found that rats distinguish between different cooperators depending on the quality of their help (Dolivo & Taborsky, 2015a).…”
mentioning
confidence: 99%